BIMBINGAN BAGI ANAK BERPERILAKU BERMASALAH DI SD NEGERI WOLIBANG - Marni S. Laure; Mehelina R. Lebo, Neziah Hinagay, Musa Famau, Yessy Maata, Petrus Mau Tellu Dony (CV. ADIBA AISHA AMIRA, 2025)
The purpose of this research at SD Negeri Woliabang (Woliabang Public Elementary School) is to facilitate positive change by identifying the root causes of behavioral issues, teaching healthy strategies, increasing self-awareness, and developing empathy. The research method used is a qualitative description, including interviews Class III homeroom teacher. The research findings are as follows: 1) The school’s approach to handling students with problematic behavior at SD Negeri Woliabang includes providing guidance, and involving parents and teachers in addressing the issues. The role of the teacher in managing student behavior at SD Negeri Wolibang is highly significant. Teachers consistently assist students in developing their attitudes, identifying their needs, and creating effective solutions for student problems. Teachers also always involve parents when addressing student issues.